Determinants of performance in the board examination for Mechanical Engineering graduates of the Nueva Vizcaya State University, Bambang campus - Dale Mark N. Bristol; Larry P. Remolazo; Ernesto B. Bausel Jr.; Jeanelyn R. Tominez; Jemimah P. Natividad (International Research Journal of Science, Technology, Education, and Management)
A culture of excellence and quality should always incorporate continuous improvement. Institutions of higher learning are the spearheads of creative minds and improve the capability and caliber of the professionals and leaders resulting from the confluence of academic and industrial relationships. A yardstick called board examination is administered to engineering graduates by the Professional Regulations Commission (PRC) to produce licensed engineers in the Philippines. Considering this, the research aims to investigate the determinants of board examination performance for Mechanical Engineering graduates of the Nueva Vizcaya State University, Bambang Campus. The data were gathered through surveys and interviews of mechanical engineering graduates and faculty members involved in board exam preparation programs. To analyze the performance details of the board examination in the Mechanical Engineering program of the Nueva Vizcaya State University, various quantitative methods such as t-test, correlation analysis, logistic linear regression, and path analysis are utilized to test the significance level between 2011 - 2015 and 2016 - 2020, who took the board examination; establish if there is any association between board examination and academic performance, and predict subject areas that affect most the performance in the board examination as well to create a mathematical prediction model in this aspect. The findings of this study would serve as a guide and an eye-opener for engineering learning institutions in determining effective strategies to improve the board exam performance of mechanical engineering graduates and as well enhance the quality of mechanical engineering education.